Molecular mechanisms of CAND2 in regulating SCF ubiquitin ligases - Kankan Wang; Lihong Li; Sebastian Kenny; Dailin Gan; Justin M. Reitsma; Yun Zhou; Chittaranjan Das; Xing Liu (Nature Communications)
Abstract Protein degradation orchestrated by SKP1·CUL1·F-box protein (SCF) ubiquitin ligases is a fundamental process essential for cellular and organismal function. The dynamic assembly of SCFs, facilitated by CAND1, ensures timely ubiquitination of diverse SCF target proteins. As a homolog of CAND1, CAND2 alone has been implicated in various human diseases, yet its functional mechanisms remain elusive. Here, we investigate the role of CAND2 in human cells and its distinct mode of action compared to CAND1. Using an array of quantitative assays, we demonstrate that CAND2 promotes SCF-mediated protein degradation as an F-box protein exchange factor. While CAND2 binds CUL1 with structure and affinity comparable to CAND1, it exhibits lower efficiency in exchanging F-box proteins. Kinetic measurements reveal a significantly higher K M for CAND2-catalyzed SCF disassembly than CAND1, which explains the lower exchange efficiency of CAND2 and is likely due to conformations of the CAND2·SCF exchange intermediate complex being less favorable for F-box protein dissociation. Our study provides mechanistic insights into the biochemical and structural properties of CAND2, as well as its role in regulating cellular dynamics of SCFs, laying a foundation for understanding contributions of CAND2 to healthy and diseased human cells.